The in-laws [videorecording (DVD)] - Hiller, Arthur; Sackheim, William; Bergman, Andrew; Falk, Peter, 1927-2011; Arkin, Alan; Libertini, Richard; Dussault, Nancy; Peyser, Penny; Golonka, Arlene; Lembeck, Michael; Smith, Paul, 1936-2012; Caridi, Carmine, 1934-2019; et al. (Criterion collection, 2003)
Dentist Sheldon Kornpett is a respectable man. He has a daughter who is about to marry the son of a very suspicious character, Vince Ricardo. Nonetheless, Vince calls on Sheldon and convinces him to go with him on a series of adventures, claiming all the while that he is a CIA agent, and that what he is doing is in national interest. Sheldon follows Vince to a South American country ruled by a very odd man, General Garcia, who talks to his hand. It seems that the dictator is involved in a scheme to counterfeit and undermine U.S. currency.